Potential and Opportunities for Using Big Data in Public Administration - Dziundziuk, Borys; Dziundziuk, Viacheslav (Law, State and Telecommunications Review, 2025)
[Purpose] The purpose of the study was to highlight the specific features of using big data and artificial intelligence in public administration. [Methodology/approach/design] Economic and statistical analysis methods were used to process the data, including the Wilcoxon statistical method for comparing trends. [Findings] It was found that the use of big data in public administration opened up new opportunities for improving the efficiency of public services through accurate analysis, forecasting, and automation of processes. However, along with these capabilities, risks were also identified, in particular, privacy issues, the possibility of information abuse, and technical issues that required careful management and security measures to minimise negative consequences. A review of the use of big data in public administration in the UK, Finland, and Singapore revealed different approaches to integrating such data into public administration. It was determined that the UK focused on transparency and citizen participation through open data, Finland in its approach focused on data security and personalisation of services, and Singapore used big data to improve infrastructure and urban planning. The selected countries demonstrated various models and strategies that outlined the main success factors and their impact on the effectiveness of public services. Based on this international experience, Ukraine was recommended to implement integrated analytical platforms for big data processing, ensure a high level of information security, and develop personalised services for citizens. [Practical implications] The results highlighted the importance of integrating advanced big data processing technologies to improve the efficiency and transparency of public administration in Ukraine. Further research may focus on adapting and implementing successful international practices of using big data in public administration, considering the specifics of the Ukrainian context.